Strategi Motivasi, Kepuasan Kerja, dan Kepemimpinan untuk Optimalisasi Kinerja Karyawan - Rahmi, Hasya Bianca (PRODUKTIF: Jurnal Kepegawaian dan Organisasi, 2024)
In competitive business, it is important to understand the relationship between motivation, job satisfaction, leadership, and employee performance. This research is to explore effective strategies in improving employee performance through these factors. This research aims to analyze motivation, job satisfaction and leadership strategies that can optimize employee performance in a quantitative approach used in this research by collecting data through questionnaires distributed to respondents. Data processing is carried out using regression analysis and other statistical tests to identify the relationship between the variables studied. work environment. The research results show that there is a significant positive relationship between motivation, job satisfaction, leadership and employee performance. Strategies that focus on increasing motivation, strengthening job satisfaction, and building effective leadership can make a significant contribution to optimizing employee performance.